Effect of Acupuncture on the Expression of Heme Oxygenase 1 and Inflammatory Factors in Rats with Intracerebral Hemorrhage - CHEN Qiuxin; KONG Ying; YU Tingting; ZHANG Yu; LIU Peng; ZHANG Xin (康复学报)
ObjectiveTo explore the effects of acupuncture at Baihui through Qubin acupoint on the expression of heme oxygenase 1 （HO-1） and inflammatory factors in rats with acute intracerebral hemorrhage from the levels of behavior, histology and molecular biology, so as to provide an experimental basis for clinical acupuncture in the treatment of intracerebral hemorrhage.MethodsA total of 108 Wistar male rats were randomly divided into sham operation group, model group, acupuncture + model group （referred to as acupuncture group）. Each group was divided into 3 subgroups according to 1 d, 3 d and 7 d, with 12 rats in each group. The rat model of intracerebral hemorrhage was established by autologous blood injection. The sham operation group received various surgical operations similar to the model group, but no blood injection was performed; the model group received intracerebral hemorrhage model production without any intervention; the acupuncture group was used to create a intracerebral hemorrhage model, and treatment began 12 hours after the model was created. The Berderson scoring method was used to determine the animal success model, and rats with a score of 1-3 were included in the experiment. The rats with intracerebral hemorrhage in the acupuncture group were treated by acupuncture Baihui through Qubin acupoint. The depth of the needle was 20 mm, and the needle was twirled at 100 r/min with small amplitude. Twist the needle once every 5 minutes, and keep the needle for 30 minutes each time, once a day. Modified Neurological Severity Score （mNSS） was used to evaluate the neurological function of rats after intracerebral hemorrhage on 1 d, 3 d and 7 d. Hematoxylin-eosin (HE) staining was used to observe the pathological changes of brain tissue. The expression of HO-1, nuclear transcription factor-κB （NF-κB）, Interleukin-1β (IL-1β), transforming growth factor-β （TGF-β） protein in hematoma tissue was detected by Western blot method at three time points of 1 d, 3 d and 7 d.Results1） There were no obvious neurological deficits in the sham operation group at all time points; the rats in the model group showed neurological deficit symptoms on the 1st day, and there were still obvious neurological deficits on the 3rd and 7th days; compared with the model group, the acupuncture group had significantly lower neurological scores at each time point （P<0.01）. 2） Normal nerve cells and glial cells were seen in the basal ganglia of rats in the sham operation group. Rats in the model group showed hemorrhage foci after the 1st day of modeling; the hemorrhage foci increased on the 3rd day, and the pathological structure of the brain tissue was obviously damaged; the hematoma area decreased on the 7th day. Compared with the model group, the acupuncture group had a lower degree of damage to the pathological structure of the brain tissue at each time point. 3） The sham operation group showed a small amount of HO-1 protein expression. The expression of HO-1 protein in the model group increased at each time point. Compared with the model group, the expression of HO-1 protein in the acupuncture group increased significantly on the 3rd and 7th day （P<0.05）. 4） In the sham operation group, a small amount of NF-κB, IL-1β, and TGF-β protein expression were seen; the expression of NF-κB, IL-1β, and TGF-β protein in the model group was significantly increased at each time point, and the relative expression was the highest on the third day; compared with the model group, the protein expression of NF-κB, IL-1β, and TGF-β in the acupuncture group was significantly reduced on 1st, 3rd and 7th day （P<0.05）.ConclusionAcupuncture can reduce the neurological deficit scores in rats with intracerebral hemorrhage, possibly by promoting the expression of HO-1 protein, inhibiting the expression of NF-κB, IL-1β, and TGF-β proteins, reducing inflammatory reactions, and exerting a protective effect on the brain.